A new multiple air beam approach for in-process form error optical measurement. (11th June 2018) - Gao, Y; Li, R
Abstract: In-process measurement can provide feedback for the control of workpiece precision in terms of size, roughness and, in particular, mid-spatial frequency form error. Optical measurement methods are of the non-contact type and possess high precision, as required for in-process form error measurement. In precision machining, coolant is commonly used to reduce heat generation and thermal deformation on the workpiece surface. However, the use of coolant will induce an opaque coolant barrier if optical measurement methods are used. In this paper, a new multiple air beam approach is proposed. The new approach permits the displacement of coolant from any direction and with a large thickness, i.e. with a large amount of coolant. The model, the working principle, and the key features of the new approach are presented. Based on the proposed new approach, a new in-process form error optical measurement system is developed. The coolant removal capability and the performance of this new multiple air beam approach are assessed. The experimental results show that the workpiece surface y ( x, z ) can be measured successfully with standard deviation up to 0.3011 µ m even under a large amount of coolant, such that the coolant thickness is 15 mm. This means a relative uncertainty of 2 σ up to 4.35% and the workpiece surface is deeply immersed in the opaque coolant. The results also show that, in terms of coolant removal capability, air supply and air velocity, the proposed new approach improves by, respectively, 3.3, 1.3 and 5.3 times on the previous single air beam approach. The results demonstrate the significant improvements brought by the new multiple air beam method together with the developed measurement system.